Implementasi Media Pembelajaran Menggunakan Augmented Reality Dengan Metode Marker Based Tracking Untuk Pengenalan Panca Indra Pada Manusia (Studi Kasus : SDN Ratu Jaya 3 Kec. Cipayung Kel. Ratu Jaya, Depok, Jawa Barat) - Rudi Aryanto; Sofa Sofiana (CV. Multi Kreasi Media, 2023)
Technological developments like today can facilitate activities in various fields, including in the field of education. In this study, developing learning media by utilizing augmented reality technology for the introduction of the five senses to elementary school students. This study aims to produce applications that can help students understand the real form of the five human senses with augmented reality technology and can make students more enthusiastic about learning and not bored. This research was conducted at SDN Ratu Jaya 3 Depok school which was attended by students and teachers. In this research data collection techniques using interviews, questionnaires, and literature study. Making this learning application with the marker-based tracking augmented reality method for learning the recognition of the five senses can display 3D objects and object information using markers and an Android smartphone. the system development model used in making this apikai is the Waterfall model SDLC (System Development Lift Cycle) method. The supporting applications used are Unity, Vuforia SDK, Blender 3D, JDK, Photoshop, Visual Studio Code, and use the C# language. application testing using the Black Box with the RTM system (Requirement Traceability Matrix) and User Acceptance Testing (UAT) using a questionnaire. Using an Android smartphone and internet network at SDN Ratu Jaya 3 school, this application can be used as a visual aid and learning tool for recognizing the five senses to students, so that students can see objects of the five senses more clearly and can more easily understand the information conveyed from this application. .